On the Study of Higher Education in Canadian Universities - Skolnik, Michael L. (Canadian Journal of Higher Education, 1991)
Although research on Canadian higher education has advanced considerably over the past few decades, the opportunities for university level study of higher education in Canada are still quite limited. Only four universities offer higher education programs; only one has a higher education department; and only a handful of other institutions offer even a course in higher education. The number of students enrolled in higher education programs in Canada is about 200, compared to about 6,000 in the United States; the number of faculty about 15 compared to 700 in the U.S. Moreover, while American higher education journals have, since the early 1970’s, regularly featured articles about university higher education programs, there has not been a single article on this subject in The Canadian Journal of Higher Education. This paper attempts to fill some of that gap by providing some basic information about the study of higher education in Canadian universities and by examining the role of these programs in the overall development of higher education research and the possible reasons for the very limited scale of such programs in Canada. The author’s conclusion is that the factor which has most limited the development of higher education studies in Canadian universities is neither insufficient student demand nor limited employment opportunities of graduates, but reluctance of Canadian universities to allocate resources for this area of study. This reluctance is attributed to the combination of the low prestige of higher education as a field of study and the lack of a strong lobby for this program area outside the university. It is suggested that - in contrast to their American counterparts - presently Canadian higher education programs have less than the minimum resources necessary to make the advances that would be required to overcome this "prestige barrier".